Traction testing of soccer boots under game relevant loading conditions - Grund, T.; Senner, V. (The Engineering of Sport 6, Volume 1 Developments for Sports, 2006)
The final goal of this research is to determine anterior cruciate ligament (ACL) tensile forces under game relevant loading conditions with respect to different types of soccer boots and different stud design. To realize the given target a combination of experimental testing and Computer Simulation was chosen. Based on the findings of previous studies and the analysis of video-recorded injury situations in soccer, a new traction test device ( Trak-Tester ) has been developed. The distinguishing feature of this device is to simulate and measure not only pure traction force between shoe and surface but also to simulate high risk loading situations such as the plant-and-cut-maneuver . The resulting forces and torque transmitted to the tibia will be measured using a 6-component-load-cell. Comparative testing concerning the amount of traction and the extent of force and torque produced with different sole designs will follow. For calculation of ACL tensile forces the experimentally determined loads transmitted to the lower leg will later be used as input data for a multi-body Computer model of the human knee. The current paper will demonstrate the need for a new traction test device and illustrate the ongoing first Steps of its development.